PARTENERIATUL – OPORTUNITATE DEOSEBITĂ DE REALIZARE - SCOBIOALĂ, director, Departamentul dezvoltare și comunicare, Genoveva (BIBLIOPOLIS, 2020)
The partnership is a phenomenon in the efficiency and the development of modern libraries. Modalities of interaction between several institutions involved in the common actions contribute to the expansion and improvement of offers, diversification of activities, the growing interest in the library.